2022
DOI: 10.1002/celc.202200373
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic‐Framework‐Based Electrochemical Nanosensor for Hydrogen Peroxide

Abstract: This Communication is dedicated to Prof. Hubert Girault on the occasion of his 65 th birthday.Electrochemical applications of metal organic frameworks (MOFs) are of considerable current interest. Due to the large surface area exposed to solution, MOFs are potentially useful electrode materials for sensing inner-sphere analytes, such as reactive oxygen species. Herein, we electrodeposited copper benzene tricarboxylate MOF (HKUST-1) into the cavity of an open carbon nanopipette (CNP) to produce a CNP-MOF nanoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Fabrication of open carbon nanopipettes.-CNPs were prepared according to the previously reported protocol. 18,21 Briefly, open nanopipettes were prepared by pulling quartz capillaries (1.0 mm o.d., 0.5/0.7 mm i.d. ; Sutter Instrument Company) with a laser pipette puller (P-2000, Sutter Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fabrication of open carbon nanopipettes.-CNPs were prepared according to the previously reported protocol. 18,21 Briefly, open nanopipettes were prepared by pulling quartz capillaries (1.0 mm o.d., 0.5/0.7 mm i.d. ; Sutter Instrument Company) with a laser pipette puller (P-2000, Sutter Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Electrode modification with CoMOF.-CoMOF electrosynthesis was conducted according to the previously published protocol 18 with some modifications. Cobalt (II) nitrate trihydrate (4.5 mmol) and sodium nitrate (100 mmol) were dissolved in 5 ml of water (solution A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, when MOFs do not have fluorescence properties, ion detection will not be possible. However, some recent work in detection revealed that, when a chemical reaction occurs within the nanopores of MOFs, the current through the holes will change significantly, and this variation of current can also be employed for the detection of ions. Moreover, using this method, Liu and co-workers successfully constructed an artificial sodium ion-selective ionic device with a selectivity ratio of Na + /K + up to 15 via growing a crown ether crystal in situ in the tip of the glass micropipette . This study opens the door for the construction of a variety of artificial ion channels with adjustable selectivity for metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…5A). 22–24 In the case of the biocomposites, CytC@H1 exhibits a similar activity than H1, while CytC@HK1 reveals a sharp activity enhancement, which is attributed to its characteristic permanent porosity that enables the transfer of substrates. Control analysis over the physical mixtures reveal that combination of CytC and H1 perform as free CytC (Fig.…”
mentioning
confidence: 98%